Implication of garnet zoning in high pressure- ultrahighpressure eclogite from Changning-Menglian suture zone, Bangbing area, Southeast Tibetan Plateau - Lu, Nannan; Wang, Guozhi; Fu, Yuzhen; Peng, Zhimin (Frontiers in Earth Science, 2022)
Major and trace element zonation patterns were determined in ultrahigh-pressure eclogite garnets from the Changning-Menglian suture, Bangbing area.Several stages of eclogite metamorphism are recorded by garnet zonation.Cores of garnets are generally darker and inclusion-rich while rims are brighter and inclusion-poor.Garnet were analyzed for major by EPMA and trace element by LA-ICP-MS. Major and trace element zonation patterns were determined in eclogite garnets from Bangbing. The results show that both major elements and rare earth elements in garnet have typical compositional bands. The major element zonation recorded the process of increasing temperature and pressure and the metamorphism of the eclogite from the core to rim, and the rare earth elements recorded different mineral chemical reactions during the formation of the garnet and its three stage of growth. Eclogites completely imply the process of rapid exhumation, cooling and depressurization after short-term peak metamorphism. The contents of some trace elements (such as Y and Sr) in garnet are controlled by major elements and mineral combinations . The formation of new minerals in the process of retrograde metamorphism affects the distribution of trace elements.